2016
DOI: 10.1242/jcs.161190
|View full text |Cite
|
Sign up to set email alerts
|

The kindlin family: functions, signaling properties and implications for human disease

Abstract: The kindlin (or fermitin) family of proteins comprises three members (kindlin-1,-2 and -3) of evolutionarily conserved focal adhesion (FA) proteins, whose best-known task is to increase integrin affinity for a ligand (also referred as integrin activation) through binding of β-integrin tails. The consequence of kindlin-mediated integrin activation and integrin-ligand binding is cell adhesion, spreading and migration, assembly of the extracellular matrix (ECM), cell survival, proliferation and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
187
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(192 citation statements)
references
References 137 publications
3
187
0
2
Order By: Relevance
“…The talin head alone can shift the integrin conformation towards an active state (Box 1), but there is increasing evidence that forces generated by actin polymerisation and myosin contraction are involved in inducing or stabilising the extended-open conformation (Comrie et al, 2015;Nordenfelt et al, 2016). This additional mechanism fits well with the discovery of other IAPs that cooperate with talin to activate integrins, such as kindlins, although the mechanism is still unclear and kindlins also cluster integrins (Moser et al, 2009;Calderwood et al, 2013;Ye et al, 2013;Rognoni et al, 2016;Georgiadou et al, 2017). Additional IAPs enhancing talinmediated activation are RIAM (Han et al, 2006;Yang et al, 2014), zasp (also known as LDB3) (Bouaouina et al, 2012) and vinculin (Lee et al, 2013), whereas other IAPs compete with talin and reduce activation, including ICAP1 (also known as ITGB1BP1) (Bouvard et al, 2003), filamin A (Kiema et al, 2006) and moesin (Vitorino et al, 2015).…”
Section: Talin In Integrin Activationmentioning
confidence: 70%
“…The talin head alone can shift the integrin conformation towards an active state (Box 1), but there is increasing evidence that forces generated by actin polymerisation and myosin contraction are involved in inducing or stabilising the extended-open conformation (Comrie et al, 2015;Nordenfelt et al, 2016). This additional mechanism fits well with the discovery of other IAPs that cooperate with talin to activate integrins, such as kindlins, although the mechanism is still unclear and kindlins also cluster integrins (Moser et al, 2009;Calderwood et al, 2013;Ye et al, 2013;Rognoni et al, 2016;Georgiadou et al, 2017). Additional IAPs enhancing talinmediated activation are RIAM (Han et al, 2006;Yang et al, 2014), zasp (also known as LDB3) (Bouaouina et al, 2012) and vinculin (Lee et al, 2013), whereas other IAPs compete with talin and reduce activation, including ICAP1 (also known as ITGB1BP1) (Bouvard et al, 2003), filamin A (Kiema et al, 2006) and moesin (Vitorino et al, 2015).…”
Section: Talin In Integrin Activationmentioning
confidence: 70%
“…Meanwhile, the F 3 subdomain of TH also recognizes the membrane-proximal residues of the integrin β CTs and is thus capable of unclasping the integrin α/β CT complex and triggering integrin activation (Wegener et al, 2007); in addition, other subdomains in TH are functionally supportive by facilitating membrane attachment (Goult et al, 2010). Besides talin, multiple lines of evidence, from model cells to genetically modified mice to human patients, have clearly shown that kindlins are also essentially involved in supporting integrin activation (Larjava et al, 2008;Plow et al, 2009;Rognoni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Kindlin2 is ubiquitously expressed, and loss of kindlin2 in mice leads to peri-implantation lethality (11). Kindlins are also involved in tumorigenesis and metastasis (19). The kindlin-associated diseases are due, at least in part, to impaired integrin activation, focal adhesion (FA) formation, and cell spreading (10,12).…”
mentioning
confidence: 99%